Advances in numerical analysis of creep effect in time-dependent deflection of light-weight concrete slabs. Issue 18 (15th September 2020) - Vakhshouri, Behnam; Nejadi, Shami; Erkmen, Emre
Abstract: Using a wide range of creep models, the experimental results of long-term deflection of lightweight concrete slabs subjected to two levels of early-age loading are investigated. Different creep models give considerably different estimation of the experimental deflection of slabs. The included factors in each creep model to simulate the experimental creep behavior of the concrete, and loading level on the slabs are the main causes of different results. Among the investigated models, the BP1 and FIBMC-2010 models including the aggregate type and concrete density is shown to be in good agreement with the experimental data in both loading levels.